PENGARUH PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN SIMULASI KOMPUTER BERBASIS INKUIRI TERHADAP PEMAHAMAN KONSEP LISTRIK DINAMIS PADA MAHASISWA IPA UNIGHA - Muhammad Saiful; Muchsin Muchsin; Hamdi Hamdi (Jurnal Sains Riset, 2022)
This research is a quantitative quasi-experimental study with a 2x2 factorial design, carried out at the Faculty of Science, Jabal Ghafur University. This study aims to determine the effect of the STAD type cooperative learning model with inquiry-based computer simulation on the understanding of the concept of direct current electricity. The subjects of this study were students of the even semester of Academic Science 2021/2022 as many as 28 Unigha Science students in the experimental class and control class. Students in both classes were further divided into two categories of initial ability, high and low. Subjects were given a pretest before learning occurred and after that was given a posttest. Analysis with two-way ANOVA at a significance level (α) of 0.05 showed a significant difference between STAD type cooperative learning with inquiry-based computer simulations and conventional learning in understanding the concept of direct current electricity with a p-value of 8.78 x 10-9, while for the initial ability category is 0.05 and for the interaction of the two variables obtained 0.60. The results of the study concluded that the STAD type cooperative learning model with inquiry-based computer simulation gave a very significant influence on understanding the concept of direct current electricity. The initial ability of physics does not give any effect, which is indicated by the absence of interaction effect between the learning model and the ability to understand the concept.Keywords: Cooperative Learning of STAD type, Initial Capability, Inquiry-based Computer Simulation, Conceptual Understanding, Direct Current Electricity.Keywords: STAD Type Cooperative Learning, Inquiry-Based Computer Simulation, Conceptual Understanding, Dynamic Electricity.